Hearing devices - Ventura, Marne (Engineering the human body., 2020)
Investigates the power of hearing devices and implants to aid and improve the lives of people with hearing loss. Discusses the types of hearing loss and new technology that has made hearing devices more effective, useful, and discreet than ever. Includes a glossary, an index, resources for more information, and text-relevant questions.